Callose in leptoid cell walls of the moss Polytrichum and the evolution of callose synthase across bryophytes - Renzaglia, Karen; Duran, Emily; Sagwan-Barkdoll, Laxmi; Henry, Jason (Frontiers in Plant Science, 2024)
Introduction Leptoids, the food-conducting cells of polytrichaceous mosses, share key structural features with sieve elements in tracheophytes, including an elongated shape with oblique end walls containing modified plasmodesmata or pores. In tracheophytes, callose is instrumental in developing the pores in sieve elements that enable efficient photoassimilate transport. Aside from a few studies using aniline blue fluorescence that yielded confusing results, little is known about callose in moss leptoids. Methods Callose location and abundance during the development of leptoid cell walls was investigated in the moss Polytrichum commune using aniline blue fluorescence and quantitative immunogold labeling (label density) in the transmission electron microscope. To evaluate changes during abiotic stress, callose abundance in leptoids of hydrated plants was compared to plants dried for 14 days under field conditions. A bioinformatic study to assess the evolution of callose within and across bryophytes was conducted using callose synthase (CalS) genes from 46 bryophytes (24 mosses, 15 liverworts, and 7 hornworts) and one representative each of five tracheophyte groups. Results Callose abundance increases around plasmodesmata from meristematic cells to end walls in mature leptoids. Controlled drying resulted in a significant increase in label density around plasmodesmata and pores over counts in hydrated plants. Phylogenetic analysis of the CalS protein family recovered main clades (A, B, and C). Different from tracheophytes, where the greatest diversity of homologs is found in clade A, the majority of gene duplication in bryophytes is in clade B. Discussion This work identifies callose as a crucial cell wall polymer around plasmodesmata from their inception to functioning in leptoids, and during water stress similar to sieve elements of tracheophytes. Among bryophytes, mosses exhibit the greatest number of multiple duplication events, while only two duplications are revealed in hornwort and none in liverworts. The absence in bryophytes of the CalS 7 gene that is essential for sieve pore development in angiosperms, reveals that a different gene is responsible for synthesizing the callose associated with leptoids in mosses.